The Effect Of Affective Commitment, Compensation, Organizational Climate On Job Satisfaction Of Diy Transportation Service Employees - Juita Tirza; Prayekti Prayekti (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the effect of affective commitment, compensation, organizational climate on employee job satisfaction at the Department of Transportation of the Special Region of Yogyakarta. The research method used in this research is descriptive quantitative using multiple regression statistical correlation to analyze the effect of the independent variable and the dependent variable on the study. The population in this study were employees at the Department of Transportation of the Special Region of Yogyakarta, with a sample of 50 respondents. The results of the study stated that affective commitment, compensation, organizational climate have a positive and significant influence on job satisfaction